Upaya Pemenuhan Kebutuhan Aktivitas Ibu Hamil Dengan Perdarahan Di Rsu Assalam Gemolong - Hartanti, Frediana Pegia; , Dr. Faizah Betty Rahayuningsih, S.Kep., M.Kes (2016)
It is proved that 25-30% of mortality case is caused by hemorrhage. Hemorrhage takes place at about 3% from all cases, among them are placenta previa and solutio placenta. The cause of hemorrhage is unclear. The physiological needs according to Abraham Maslow is primary basic needs that must be met to maintain the survival for human. If the needs cannot be met, it will influence other needs. ctivity intolerance related to bedrest caused a weakness in general. It is caused by the supply of oxygen with the use signified by exhaustion, abnormal responses on the ctivities signified by uncomfort. A total bedrest is suggested for a client with antepartum hemorrhage to maintain the fetus in order to avoid prematurity. This research aimed at increasing the fulfilment of activity needs for a pregnant woman with hemorrhage. This research used a descriptive method through a case study approach. The research was conducted in RSU Assalam Gemolong Sragen with the sample was Mrs. H. The data collection was obtained from interview, direct observation, physical examination and diagnostic examination. Intervention was conducted by monitoring the vital signs, helping the client in meeting the daily activity needs, suggesting the client to take a rest, suggesting the client to sleep with an aslant position, and monitoring the nutrition intake. Implementation was conducted for 3 days on 29 - 31 March 2016. After conducting nursing cares for 3 days, it was obtained a result that the client had an increase in meeting the activity needs independently. The writer hopes that the pregnant woman who suffers from hemorrhage with placenta previa checks his pregnancy routinely, therefore, the risk of premature birth can be minimized.